Neo-transitional economics - Jamilov, Rustam; Akbar, Yusaf H., 1969- (International finance review ;, 2015)
Post-transition countries are coming of age and are approaching the status of fully-blown developing states. While the main problems highlighted in a classical transition storyline, such as large-scale privatization, institutional formation, and private sector establishment have largely been solved, the recent financial crisis has revealed fresh challenges which demand maximum differentiated attention. Such important contemporary issues as capital markets formation, monetary transmission mechanism, economic integration, financial sector sophistication, remittance management, social welfare reform, and competitive fringes remain to be tackled in a systematic, policy-oriented manner. "Neo-transitional economics" fills this escalating literature gap by presenting a comprehensive collection of viewpoints from the established scholars and practitioners of the field. The ultimate goal of this book is to offer an all-encompassing policy toolkit for a successful overcoming of all contemporary challenges that lie ahead in the age of neo-transitional economics.